1999
DOI: 10.1146/annurev.matsci.29.1.381
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Tunneling in Ferromagnetic Junctions

Abstract: ▪ Abstract  Based on the spin conservation in electron tunneling across an insulator (I) and the spin polarization of conduction electrons in ferromagnets (FM) established by Meservey and Tedrow, Jullière put forward a quantitative model (1975) showing that tunneling in FM-I-FM junctions should lead to a large junction magnetoresistance (JMR). This conjecture was realized with repeatable results only in 1995, and since then JMR values >30% have been achieved at room temperature. This phenomenon has tremendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
154
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(166 citation statements)
references
References 127 publications
9
154
1
2
Order By: Relevance
“…These results are in fair agreement with earlier work. 7,8 To study the barrier dependence of P, we replace the AlO x barrier by another insulator. In general, for clear observation of the Zeeman-split superconducting density of states, the insulator needs to meet two requirements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in fair agreement with earlier work. 7,8 To study the barrier dependence of P, we replace the AlO x barrier by another insulator. In general, for clear observation of the Zeeman-split superconducting density of states, the insulator needs to meet two requirements.…”
mentioning
confidence: 99%
“…This mechanism plays a role in magnetic tunnel junctions with antiferromagnetic barriers such as NiO and CoO where only relatively small TMR effects are obtained. 8 We have studied the oxidation state of the ferromagnet in our junctions with in situ XPS. For careful investigation of the interface, samples are used of which the thickness of the ferromagnetic electrode deposited on top of the barrier is only 4 Å.…”
mentioning
confidence: 99%
“…The electrostatic potential energy qV provided by voltage bias V tunes the energy of hot electrons emitted from the cathode, and the exponential energy dependence of quantummechanical tunnelling assures a narrow distribution. Because of its robust insulating native oxide, aluminium (Al) is often employed during TJ fabrication; although in principle any insulator can be used, it has been empirically found that the best are Al x O, MgO and AlN [16,17]. Some of the hot electrons thus created can travel without inelastic scattering (i.e.…”
Section: Hot Electron Generation and Collectionmentioning
confidence: 99%
“…This issue can be of paramount concern for spininjection from a ferromagnet into a semiconductor or across an insulator, as for tunnel junctions, where the spin polarization at the interface is one of the parameters that determines the net spin current across the interface [127]. For example, a magnetically dead metallic layer at the tunnel junction interface can destroy the polarization of the transmitted current by serving as a source of unpolarized spins [128]. Magnetic dead layers have been directly observed in Fe/Si multilayers using polarized neutron reflectivity [129], and in Ni/Pt multilayers via X-ray circular dichroism [130].…”
Section: Proximity Effects: Induced Magnetizationmentioning
confidence: 99%